Segmentation and Holocene Behavior of the Middle Strand of the North Anatolian Fault (NW Turkey). Issue 11 (1st November 2021) - Benjelloun, Y.; de Sigoyer, J.; Garambois, S.; Carcaillet, J.; Klinger, Y.
Abstract: The North Anatolian Fault (NAF) in the Marmara region is composed of three parallel strands all separated by ∼50 km. The activity of the middle strand, which borders the southern edge of the Marmara Sea, is much debated because of its present‐day very low seismicity. This contrasts with historical, archeological and paleoseismological evidence, which suggest several destructive earthquakes have occurred during the last 2000 years. Our study aims to better constrain seismic hazard on the middle strand by exploring its Holocene paleoseismicity. For this, we mapped 148 km of the eastern part of the middle strand, using high‐resolution satellite imagery. A series of landforms offset by the middle strand activity have been systematically measured to recover the past ruptures. Three Late Pleistocene‐Holocene terraces have been dated with the terrestrial cosmogenic nuclide method, constraining a horizontal slip rate of 4 . 4 − 2.8 + 10.6 mm/yr. The statistical analysis of the offsets evidences several major ruptures preserved in the landscape, with coseismic lateral displacements ranging between 3 and 6.5 m. This corresponds to Mw ∼7.3 earthquakes able to propagate along several fault segments. Historical seismicity and paleoseismology data suggest that the last large earthquakes along the middle strand of the NAF (MNAF) happened in 1065 CE and between the 14th and 18th centuries CE. Since then, the MNAF may have accumulated enough stress to generate a destructive rupture. Key Points: Systematic measurements of horizontal cumulative offsets along the middle strand of the North Anatolian Fault Statistical analysis of the data set allows to identify the last large ruptures along the fault and the associated slip per‐segment Comparison with independent constraints on past earthquakes leads to discuss past rupture scenarios